The pledge and charitable contract in the tradition "El alacrán de fray Gómez" - Rodríguez Chávez, Iván (2019)
It is possible to draw information about aspects of reality that belong to different cultural orders from both the traditions separately or as a compilation, including the ones related to science, this is the case of the legal field. In the tradition El Alacrán de Fray Gómez, one can find this possibility with the presence of specifically two contracts: a gratuitous contract and a pledge. In this paper, both contracts will be analyzed in a basic level with an educational approach, becoming the tradition itself a case aimed to students that are in the early stage of their vocational training.